Pluggable Authentication Modules : the definitive guide to PAM for Linux sysadmins and C developers : a comprehensive and practical guide to PAM for Linux : how modules work and how to implement them /: the definitive guide to PAM for Linux sysadmins and C developers : a comprehensive and practical guide to PAM for Linux : how modules work and how to implement them. (2007) - Unknown
No abstract available